Empire, colonialism, and the human sciences : troubling encounters in the Americas and Pacific - Warren, Adam, Ph.D; Rodríguez, Julia, 1967-; Casper, Stephen T. (Cambridge University Press, 2024)
In this bold reconsideration of the human sciences, an interdisciplinary team employ an expanded theoretical and geographical critical lens centering the notion of the encounter. Drawing insights from Indigenous and Latin American Studies, nine case studies delve into the dynamics of encounters between researchers, intermediaries, and research subjects in imperial and colonial contexts across the Americas and Pacific. Essays explore ethical considerations and knowledge production practices that prevailed in field and expedition science, custodial institutions, and governance debates. They reevaluate how individuals and communities subjected to research projects embraced, critiqued, or subverted them. Often, research subjects expressed their own aspirations, asserted sovereignty or autonomy, and exercised forms of power through interactions or acts of refusal. This book signals the transformative potential of Indigenous Studies and Latin American Studies for shaping future scholarship on the history of the human sciences. This title is also available as Open Access on Cambridge Core.